THU0003 Fine-mapping of autoimmune susceptibility LOCI using immunochip identifies novel susceptibility LOCI for psoriatic arthritis. (23rd January 2014) - Bowes, J.; Ho, P.; Korendowych, E.; McHugh, N.; Packham, J.; Bruce, I.N.; Barton, A.
Abstract : Background: Psoriatic arthritis (PsA) is a chronic inflammatory joint disease that typically accompanies psoriasis vulagris (PsV). Both conditions are considered to be complex diseases with both genetic and environmental susceptibility factors. Genome-wide association studies (GWAS) have identified a number of genetic susceptibility loci for both diseases. Comparing GWAS results performed in many common autoimmune diseases has revealed an extensive overlap in the genetic liability between autoimmune diseases in general. Objectives: Based on the observed sharing of susceptibility loci across autoimmune diseases, the aim of this project is to identify novel susceptibility loci for PsA by fine-mapping all the currently confirmed susceptibility loci for 12 autoimmune diseases. Methods: Data was available for 929 PsA cases and 4537 healthy controls genotyped using the Immunochip Illumina iSelect array at the Sanger Centre (www.sanger.ac.uk ). Control data was sourced from the WTCCC (www.wtccc.org.uk ). This custom array was designed to comprehensively fine-map confirmed autoimmune susceptibility loci and contains 196, 524 SNPs covering approximately 200 candidate regions. A strict SNP-focused quality control process was applied to the dataset followed by single point analysis using the Armitage test for trend. Results: Association analysis of 182, 883 high quality SNPs in 862 cases and 4306 controls robustly detected association to previously confirmed PsA risk loci; HLA-C (p=8.2×10 -35 ), IL23R (p=8.4×10 -8 ) and TRAF3IP2 (p=2.8×10 -7 ), IL12B (p=6.5×10 -6 ). In addition we find convincing evidence to support association to a number of novel loci not previously reported for PsA, including; 17q21 (ptrend =3.3×10 -05, SMARCE1), 18p11 (ptrend =2.0×10 -05, PTPN2), 11q23 (ptrend =1.4×10 -05, TREH), and 19p13 (ptrend =9.8×10 -05, TYK2) . Interestingly, we also find convincing evidence for association to the CARD15 gene, supported by multiple SNPs. Conclusions: The preliminary single point analysis of an autoimmune loci fine-mapping dataset identifies a number of potential novel loci for PsA susceptibility. Validation of these results is currently underway in an independent sample collection. Single-point analysis will be followed by analyses to indentify independent effects within the previously identified and newly discovered loci. Disclosure of Interest: None Declared